2016
DOI: 10.1186/s13756-016-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin-induced eosinophilic pneumonia - a systematic review

Abstract: PurposeEosinophilic pneumonia comprises a group of lung diseases in which eosinophils appear in increased numbers in the lungs and sometimes in the bloodstream. Several case reports link daptomycin use to this phenomenon.SummaryWe performed a systematic literature review to identify cases of eosinophilic pneumonia associated with daptomycin use. Relevant studies were identified by searching Pubmed/Medline, EMBASE, Google Scholar, Cochrane Database of Systematic Reviews, and Clin-Alert from inception to May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…AEP may be difficult to recognize due to its delayed presentation. One systematic review found the mean duration of daptomycin therapy prior to the development of symptoms to be 2.8 ± 1.6 weeks, with one study reporting presentation of symptoms as late as 6 weeks into therapy [9,12]. In the presented case, the patient became symptomatic after 2 weeks of daptomycin therapy and met all diagnostic criteria as established by the FDA.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…AEP may be difficult to recognize due to its delayed presentation. One systematic review found the mean duration of daptomycin therapy prior to the development of symptoms to be 2.8 ± 1.6 weeks, with one study reporting presentation of symptoms as late as 6 weeks into therapy [9,12]. In the presented case, the patient became symptomatic after 2 weeks of daptomycin therapy and met all diagnostic criteria as established by the FDA.…”
Section: Discussionmentioning
confidence: 78%
“…In the case of daptomycin-induced AEP, it is thought that the accumulation of the drug within a pulmonary surfactant plays a key role in the induction of an inflammatory reaction [6]. In reported cases, dosing is significantly varied, suggesting that the development of AEP may occur at any dose, however, among patients who develop AEP, those receiving higher doses had a shorter time to develop [6,9]. Additionally, elevated serum concentration due to chronic kidney disease may play a role in some cases, although a correlation between serum levels of daptomycin, and accumulation within pulmonary surfactant has not been definitively established [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corticosteroid is believed to rapidly reverse the inflammation and thereby improve the hypoxia [8]. Patients are usually started on intravenous methylprednisone 60–125 mg every 6–8 h, transitioned to oral prednisone 40–60 mg daily with clinical improvement and is tapered over 2–6 weeks to avoid relapse [8,10]. …”
Section: Discussionmentioning
confidence: 99%